Genetic Diversity and Differentiation of Sand Crab (Albunea symmysta) (Crustacea: Decapoda: Hippoidea) from Java and Papua, Indonesia - Putri, Vinna Windy; Widayati, Kanthi; Wardiatno, Yusli; Farajallah, Achmad (HAYATI Journal of Biosciences, 2024)
In Indonesia, the sand crab Albunea symmysta distribution includes Java, Sumatra, and Moluccas. Populations are assumed to be differentiated between western and eastern Indonesia due to the Wallace line; however, no information on the genetic diversity and differentiation of A. symmysta in Indonesia is available. This study was conducted to clarify the genetic diversity and differentiation of A. symmysta in Indonesia. During the sampling campaign, A. symmysta specimens were found only in Java and Papua. Genetic analysis based on the 643-bp fragment of the partial COI gene from 32 individuals revealed significant genetic differentiation between the Java and Papua populations (FST = 0.94, p < 0.005). The haplotype connectivity of the five A. symmysta sampling sites revealed a two-clade network. Based on analysis of molecular variance, most of the variation was found among populations (94.21%) rather than within populations (5.79%). Tajima's D and Fu's FS values indicated a population expansion. Overall, the findings support a high level of differentiation between the Java and Papua A. symmysta populations, suggesting the separation of population stocks due to low connectivity.